Use of white sweet clover (Melilotus albus Medik.) as a green fertilizer, effect on soil conditions and productivity of subsequent cultivation (Semiárida, 2019)
Potential production of many soils of semiarid regions has been significantly reduced by agriculture increasing, which implies absence of crop rotations, inadequate nutrient replenishment and reduction of organic matter (OM) content. Incorporation of green manure crops to the soil can be a tool to mitigate these processes. The aim of this study was to evaluate the effect of using annual legume (Melilotus albus Medik.) as green manure on soil fertility conditions and yield of dry matter (DM) and crude protein (CP) of subsequent crops in sandy loam soils of moderate fertility (2.4% OM), typical of the Semiarid Pampean Region of Argentina. Two treatments, one with legume cut simulating grazing, and the other with legume incorporated to soil, were compared with a control without legume. There was a positive effect of green manure on MS and PB yield of subsequent rye crop. In addition, residual level of soil nitrates was higher in green manure treatments than in the control. Rye crop probably was able to use only partially these nutrients due to water deficit during the growing season. Regarding the soil OM content there were no differences among treatments. This lack of response might have been due to o low rate of decomposition of green manure, or because released nitrates were leached by heavy rains that occurred in February and March. These inconsistencies in the results suggest the need to assess the rate of composition of the biomass incorporated as green manure and replicate the studies on low fertility soils, also common in our semiarid region.
Keywords: organic matter; rye; soil fertility; forage production